Efektivitas Program Rasa Sejiwa Sebagai Bentuk Inovasi Pelayanan Publik Terkait dengan Permasalahan Orang dalam Gangguan Jiwa di Kecamatan Nanggalo, Kota Padang - Yoga Pratama; Nora Eka Putri; Rizki Syafril (Jurusan Ilmu Administrasi Negara, 2022)
This research is motivated by the problem that there are still many people with mental health disorders in Padang citywhich do not get treatment to overcome their illness and roam freely on the streets with a fairly low level of economy and education and some are not taken care of by their families. One of the ways we can help people who have mental health problems in Padang city, especially in Nanggalo District, we can see with the existence of a new idea or innovation of basic mental health public services carried out by the Nanggalo Health Center with the name Rasa Sejiwa Group with Ibu Fitri Diah as the originator and implementer.The Rasa Sejiwa Program itself was officially launched on February 13, 2017, with Kurao Pagang subdisrict as a pilot program. The Rasa Sejiwa program was created to improve medication adherence for people with mental health disorders, to provide assistance and health services for mental patients as well as socialization and counseling to the general public. The Rasa Sejiwa program in the Nanggalodistrict is expected to be able to overcome problems related to people who do not have money to go to the hospital and reduce the number of patient with mental health disorder who are neglected on the streets.